Tele-operated laboratory for teaching logistics operations (2015)
The link between academia, government, and business to improve the development and appropriation of knowledge in certain topics, such as logistics, is being promoted in Colombia. One of the key issues of teaching logistics is try to bring to actual work contexts, problems that can be handled by people who do not have experience. The incorporation of Information and Communications Technologies (ICT) in academic environments supports the training of professionals in different fields. The tele-operated laboratory for logistics operations called Internet2 way [TELEOPLOGIS] is a project focused on the development and implementation of a remote laboratory where an integrated and didactic manufacturing cell, some robot manipulators, and specific pieces of software are used for the teaching of logistics operations. This laboratory includes the development of guidelines and academic workshops with two approaches: teleoperation systems for discrete events, and manufacturing cells that transform the cell nodes into elements of logistics operations. We achieved acceptable results in both remote operations and in practices that currently are in progress.